PENGARUH MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR PESERTA DIDIK - Yuliana .Yuliana; Sunarwin Sunarwin; Kartini Rahman Nisa (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
The research aimed to know the effect of example non example model of students learning outcomes with acid base solution subject at theMAS At-Taqwa Beru in even semesterof the 2020-2021 academic year. Pre-experiment used as research method with one group pre-test post-test as the research design. The studyused population from students of class XI MIA MAS At-Taqwa Beru, and used purposif sampling method, so class XI MIA which are 18 students were a research sample. Data analysis using tcount test, and first, descriptive statistical analysis and data requirements testing. Data requirements test results, where the data is normal and homogeneous. Based on the testing of the hypothesis carried out, obtained tcount of 3,6920 and ttable of 1,6957. The results tcount> ttable, so H0 is rejected and H1 is accepted. The conclusion of this research was theexample non example model influenced student learning outcomes